Comparison of thermal responses, reproductive biologies, and population growth potentials of the squash bug egg parasitoids Ooencyrtus anasae and O. sp. (Hymenoptera: Encyrtidae) - Tracy, J. L; Nechols, James R. (My University, 1988)
Laboratory investigations of the gregarious squash bug egg parasitoids Ooencyrtus anasae (Ashmead) and O. sp. were conducted at 20.8, 23.0, and 26.6°C. Females of both species emerged with undeveloped ovaries. Oöcyte development proceeded during the preovipositional period (ca. 35 h at 26.6°C) but did not exceed half of the total fecundity at initial oviposition. Preovipositional periods, time to peak oviposition, and time to 75% oviposition were generally similar for both parasitoids at 20.8°C. However, reproductive responses differed at temperatures above 20.8°C. In O. anasae, oviposition occurred significantly earlier, and at a similarly higher rate, at 23.0 and 26.6°C than at 20.8°C, whereas significant changes in preovipositional and ovipositional biology of O. sp. occurred only after an increase from 23.0 to 26.6°C. O. sp. had a significantly higher fecundity and longer ovipositional period at each temperature than did O. anasae. Mean fecundities did not change significantly with increasing temperature. Both parasitoids had an unusually long postreproductive period (ca. 1 mo) and a longevity of 40 to 50 d. At 26.6°C, O. sp. had higher gross and net reproductive rates than O. anasae. However, O. anasae had a shorter generation time (21.4 versus 23.8 d) and higher innate capacity for increase (0.146 versus 0.134).
Citation: Tracy, J., & Nechols, J. (1988). Comparison of Thermal Responses~Reproductive Biologies and Population Growth Potentials of the Squash Bug Egg Parasitoids Ooencyrtus anasae and O. sp. (Hymenoptera: Encyrtidae). Environmental Entomology, 17(4), 636–643. https://doi.org/10.1093/ee/17.4.636
Keywords: Insecta; Ooencyrtus; Anasa tristis; Biological control; Squash bug